Digitalization of Education and Challenges of Digital Policy: Study on Junior High School Students in Denpasar City - Suandayani, Dewa Ayu; Suastra, Wayan; Atmaja, Ananta Wikrama Tungga; Tika, I Nyoman (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2026)
he rapid expansion of educational digitalization has transformed the ways individuals access knowledge, engage with learning environments, and construct their social identities. In Denpasar, digital penetration is particularly high, with nearly all junior high school students owning and using smartphones as part of their daily routines. Nevertheless, this access has not been accompanied by adequate levels of digital wisdom—the critical, ethical, and responsible use of technology. As a result, a new form of digital divide emerges, known as the digital wisdom gap, wherein students possess technological access but lack the capacity to utilize it meaningfully for cognitive growth and character development. This study contextualizes the global issue of educational digitalization within the local realities of Denpasar and analyzes it through the philosophical frameworks of ontology, epistemology, and axiology. The findings reveal that unwise smartphone use impacts students’ identity formation, ways of knowing, and value orientation. The article offers humanistic and educationally grounded solutions involving digital literacy education, character formation, digital pedagogy empowerment, and strengthened family–school collaboration to foster digital wisdom from an early age.